2014
DOI: 10.1016/j.jfda.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Clove (Syzygium aromaticum) ingredients affect lymphocyte subtypes expansion and cytokine profile responses: An in vitro evaluation

Abstract: Clove (Syzygium aromaticum) has been used in folk medicine in many disorders. The present work aimed to investigate effects of clove essential oil as eugenol and water soluble ingredients on mouse splenocytes. Clove extracts were harvested and in different concentrations (0.001-1000 μg/mL) were affected to splenocytes and also phytohemagglutinin (PHA = 5 μg/mL) and lipopolysaccharide (LPS = 10 μg/mL) activated splenocytes; then splenocytes proliferation assayed using the MTT ([3-(4, 5-dimethylthiazole-2-yl) -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…Essential oils with lower content of eugenol are cinnamon oil (Cinnamomum altissimum, Cinnamomum verum, or Cinnamomum cassia)-1.2-14.7% [6][7][8][9][10] and laurel oil (Laurus nobilis)-1.4-2.2% [11]. These oils rich in eugenol are used in dietary supplements, cosmetics, aromatherapy, and phytotherapy, due to their anesthetic, antifungal, and insecticidal properties [7][8][9][10][11][12][13][14][15].…”
Section: Phenolic Terpenoids: Eugenol Carvacrol and Thymolmentioning
confidence: 99%
“…Essential oils with lower content of eugenol are cinnamon oil (Cinnamomum altissimum, Cinnamomum verum, or Cinnamomum cassia)-1.2-14.7% [6][7][8][9][10] and laurel oil (Laurus nobilis)-1.4-2.2% [11]. These oils rich in eugenol are used in dietary supplements, cosmetics, aromatherapy, and phytotherapy, due to their anesthetic, antifungal, and insecticidal properties [7][8][9][10][11][12][13][14][15].…”
Section: Phenolic Terpenoids: Eugenol Carvacrol and Thymolmentioning
confidence: 99%
“…In this study, ethanol extract and eugenol of S. aromaticum in 10 and 50 µg mLG 1 of concentration showed IL-6 inhibitory activity. Another study also confirmed that S. aromaticum could inhibit IL-1β and IL-6 production after LPS-stimulated cells (Bachiega et al, 2012;Dibazar et al, 2014a). The eugenol as main component of S. aromaticum also could suppress IL-6 in LPS-stimulated macrophage (Rodrigues et al, 2009;Miguel, 2010).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have reported that phytochemical content of S. aromaticum exerts pharmacology actions including antioxidant, hypoglemic and anti-inflammatory activities (Jung et al, 2012). Eugenol as the main ingredients of S. aromaticum have been shown to modulate some immune response, including anti-inflammatory effects (Ko et al, 1995;Dibazar et al, 2014a). In this study, we have evaluated the anti-inflammatory potential of ethanol extract and eugenol of S. aromaticum flower bud extract through IL-1β, TNF-α, NO and IL-6 inhibitory activity assays in LPS stimulated-murine macrophage cell line (RAW 264.7).…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment, eugenol, when used to treat mouse splenocytes in vitro, reduced PHA-stimulated splenocyte proliferation, but enhanced LPS-stimulated cell expansion. IFNγ release was suppressed, and IL-4, IL-10, and transforming growth factor beta (TGFβ) secretions were induced in splenocytes suggesting, according to the authors, that eugenol could enhance the humoral immune response by shifting the cytokine pattern toward T helper 2 responses [26].…”
Section: In Vitro Investigationsmentioning
confidence: 98%
“…Allium sativum (garlic) [22] Eucalyptus globulus (eucalyptus) [23,24] eugenol (from Syzygium aromaticum, clove) [25,26] Ferula iliensis [27] frankincense EO (derived from Boswellia carterii) [28] Lavandula angustifolia (lavender) [29] Pituranthos tortuosus [30] Schinus molle [31] Syzygium cumini (jambolão) [32] Thymus vulgaris (thyme) [33] In Vivo Pre-Clinical Studies…”
Section: In Vitro Investigationsmentioning
confidence: 99%